Rhein Induces a Necrosis-Apoptosis Switch in Pancreatic Acinar Cells. (13th May 2014) - Zhao, Xianlin; Li, Juan; Zhu, Shifeng; Liu, Yiling; Zhao, Jianlei; Wan, Meihua; Tang, Wenfu
Abstract : Objectives . The Chinese herbal medicine Da-Cheng-Qi decoction can regulate a necrosis-apoptosis switch in injured pancreatic acinar cells. This study investigated the effects of rhein, a component of this medicine, on a necrosis-apoptosis switch in pancreatic rat AR42J cells. Methods . Cerulein-treated AR42J cells were used. After pretreatment with 479, 119.8, or 29.9  μ g/L rhein, cells were cocultured with rhein and cerulein (10 −8  M) for 4, 8, or 16 h. Apoptosis and necrosis were examined using annexin V and propidium iodide costaining. Mitochondria-dependent apoptosis-associated proteins were examined using enzyme-linked immunosorbent assays and western blotting. Results . Few cells died in untreated samples. The number was significantly higher in 16-h-cerulein-treated samples and treatment with 479  μ g/L rhein most effectively increased the apoptotic-to-necrotic cell ratio (P < 0.05 ). In cerulein-treated cells, rhein increased the concentrations of p53, cytochrome C, and caspase-3, and increased the Bax/Bcl-2 ratio in a time- and dose-dependent manner, with the maximum effect in cells treated with 479  μ g/L rhein for 16 h (P < 0.05 ). Conclusions . Rhein induces the necrosis-apoptosis switch in injured pancreatic acinar cells in a time- and dose-dependent manner. Mitochondria-dependent apoptosis signaling pathways might play an important role in this effect.